Environmental, Social, And Governance Disclosure on Firm Value: The Moderating Role of Profitability - Lina, Lina; Rinaldy, Nigel William (Jurnal Akuntansi, 2025)
Purpose – This study aims to empirically prove the positive influence of environmental, social, and governance disclosure on firm value in companies listed on the Indonesia Stock Exchange. In addition, this study also wants to empirically prove whether profitability can strengthen the influence of environmental, social, and governance disclosure on firm value. Design/Methodology/Approach – Using environmental, social, and governance disclosure data provided by the Bumi Global Karbon Foundation, this study uses 213 data points from 2018 to 2021. Hypothesis testing uses multiple linear regression and moderated linear regression. Findings – The results of the study indicate that environmental, social, and governance disclosure has a positive influence on firm value. Meanwhile, profitability has not been proven to strengthen the influence of environmental, social, and governance disclosure on firm value. Research Limitations/Implications – The number of observations on the environmental, social, and governance index is limited to environmental, social, and governance index data from the Bumi Global Karbon Foundation only. The determination of environmental, social, and governance disclosure scores is not yet uniform, so environmental, social, and governance disclosure standards are not yet fully used universally. Keywords: Environmental, Firm Value, Governance, Social, Profitability